Understanding the role of Brd4 in the maintenance of human embryonic stem cells. - Lim, Michelle Gek Liang. (2010)
Brd4 is a bromodomain protein of the BET family and has been implicated in the cell cycle, transcription, and epigenetics. While Brd4 has been studied in mouse cells and HeLa cells, its role in human embryonic stem cell (hESC) has not been elucidated. In the present study, we investigated the role of Brd4 in the maintenance of self-renewal in hESC. By conducting cell number and viability assays on Brd4 knockdown and overexpressing hESCs, we found that cell proliferation in these cells was reduced and they exhibited slower growth as compared to the control. Data from the EdU (5-ethynyl-2´-deoxyuridine) proliferation assay revealed that these knockdown and overexpressing hESCs had reduced cell proliferation. Furthermore, analysis of cell cycle regulatory proteins—cyclin D1, CDK6, and p15—showed that G1/S progression was inhibited. Taken together, our findings suggested that Brd4 knockdown and overexpression may have some effect on cell cycle regulation in hESC. In conclusion, this presented work suggested that a precise Brd4 level is essential to maintaining the self-renewal of hESC.